The golden couple - Hendricks, Greer; Pekkanen, Sarah (New York : St. Martin's Press, 2022)
"The Golden Couple is the next electrifying novel from Greer Hendricks and Sarah Pekkanen, the #1 New York Times bestselling author duo behind You Are Not Alone, An Anonymous Girl, and The Wife Between Us. If Avery Chambers can't fix you in 10 sessions, she won't take you on as a client. Her successes are phenomenal--she helps people overcome everything from domineering parents to assault--and almost absorb the emptiness she sometimes feels since her husband's death. Marissa and Mathew Bishop seem like the golden couple--until Marissa cheats. She wants to repair things, both because she loves her husband and for the sake of their 8-year-old son. After a friend forwards an article about Avery, Marissa takes a chance on this maverick therapist, who lost her license due to controversial methods. When the Bishops glide through Avery's door and Marissa reveals her infidelity, all three are set on a collision course. Because the biggest secrets in the room are still hidden, and it's no longer simply a marriage that's in danger"--
Keywords: Novels